Catching Young Writers in the Act of Becoming - Schaefer Walton, Sarah (Journal of Juvenilia Studies)

(untitled) (International Society of Literary Juvenilia, 2026)
This short essay, a contribution to the issue's Editor's Column on the theme "Surveying Our Spacious Field," considers what we miss when juvenilia slip past our notice. Drawing on experiences with John Murray’s early travel writings and the challenges of teaching literature to contemporary students, the essay argues that juvenilia studies foster empathy, broaden literary engagement, and make space for students to see their own developing voices reflected in the past. Embracing youthful writing invites a more dynamic, inclusive understanding of literary history.